Analisis Pengukuran Kinerja Perusahaan Dengan Menggunakan Pendekatan Balanced Scorecard Pada Famous Bridal Art Collection Kota Probolinggo - Seger Priantono (Fakultas Ekonomi Universitas Panca Marga, 2016)
This research was conducted at the Famous Bridal Art collcetion in Kota Probolinggo with research objects such as Corporate Performance Measurement Analysis Using Balanced Scorecard Approach. This is done with the aim of analyzing the measurement of company performance with the balanced scorecard pendeketan Bridal Famous Art Collection in Kota Probolinggo, for the researchers to formulate the problem